globalization the internal dynamic - Paul Kirkbride, Karen Ward (JOHN WILEY & SONS, LTD)
The original idea for this book and the companion volume (Kirkbride, P.S. Globalization: The External Pressures, Wiley, 2001) came from Kate Charlton, then Director of Corporate Development and Paul Pinnington, Stream Director for Tailored Programmes. Kate and Paul were convinced that Ashridge had a wealth of talent that could be brought to bear on the topic of globalization and so the resulting works owe a debt to their vision. They had initiated discussions with publishers and Paul Kirkbride’s role, as newly appointed Research Fellow, was to bring the books to fruition. Paul was solely responsible for the first book but managed to recruit Karen Ward to help edit the second book. Editors of a collection such as this owe a debt of gratitude to the individuals who volunteered to provide chapters, often having to fit writing into a very busy teaching or consulting schedule. Thanks therefore to Paul Pinnington, Karen Ward, Bob Westwood, Samreen Khan, Andrew Ettinger, Cath Redman, Stefan Wills, Phil Hodgson and Randall White for their sterling contributions.